THE IMPACT OF FATIGUE ON ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION AMONG EMPLOYEES IN THE PHARMACEUTICAL INDUSTRY IN ATHENS - Paraskevi Theofilou; Sofia Zyga; Charalampos Economou; David Liakopoulos; Foteini Tzavella, (Current Journal of Human Resource Management (CJHM), 2023)
Fatigue is a growing concern among employees in the pharmaceutical industry, which can affect their physical and mental health, as well as their job satisfaction and organizational commitment. This cross-sectional study aimed to investigate the relationship between fatigue, organizational commitment, and job satisfaction among 102 employees of different specialties in Athens. Participants completed three questionnaires: the Fatigue Assessment Scale, the Meyer and Allen Organizational Commitment Questionnaire, and the Employee Satisfaction Inventory. Results showed a significant correlation between fatigue and various dimensions of organizational commitment and job satisfaction, and fatigue was also identified as a predictor for both. These findings highlight the importance of considering the factor of fatigue in research and interventions aimed at enhancing organizational commitment and job satisfaction in the pharmaceutical industry.The study also suggests that working conditions, fair compensation, and a positive work environment are important factors in increasing employee satisfaction and commitment in this industry. Limitations of the study include the relatively small sample size and the exclusion of employees with psychiatric disorders. Future research should focus on investigating other factors that contribute to fatigue, organizational commitment, and job satisfaction in larger samples from different pharmaceutical companies